Teaching the history of Catalonia: past, present and 'futures'. (1st May 2013) - Fernández, Antoni Santisteban
The history which is taught in Catalan schools is not on the margin of the political, economic and social situation which is being shared by those living in Catalonia. There is an on-going debate about citizenship between the Catalans and the Spanish, which has had a major impact in the media, and has had repercussions for the future of Catalonia within the Spanish state. Teaching the history of Catalonia and Spain is an issue that has a strong resonance within this debate. The problem is not new and has deep historical roots. It has re-emerged, on the one hand, because of the attitude of the state government, which represents the most centralist Spanish nationalism. Moreover, the current economic situation has made the latent problem even more urgent. However, the debate has also served to mask other important problems.